Contributing Factors to Increased Left Ventricular End-Diastolic Volume in COVID-19 ICU Patients in Sanglah Hospital: A Study on Galectin-3 - Lolobali, Marilaeta Cindryani; Widnyana, I. M. G.; Wulansari, Ni Made Ayu; Wibhuti, Ida Bagus Rangga; Wiryana, Made; Sedono, Rudyanto; Heriwardito, Aldy (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Coronavirus disease 2019 (COVID-19) is a respiratory disease that has become the largest pandemic and also could put the heart at risk of dysfunction. Galectin-3 is involved in the inflammatory process that continues with remodeling and eventually fibrosis. Using galectin-3 examination, we could predict the possible worsening of heart function and evaluate data on influencing factors for increased left ventricular end-diastolic volume (LVEDV) which could later progress to heart failure. METHODS: This is an observational prospective analytic study in the COVID-19 ICU of Sanglah Hospital, Bali, Indonesia. The study was conducted from June to October 2021. All research subjects had their blood samples taken for galectin-3 levels examination using enzyme-linked immunosorbent assay (ELISA). Subjects were also evaluated for left ventricular end-diastolic volume (LVEDV) with echocardiography, SOFA scores, and troponin I levels. Subjects were treated with COVID-19 standard protocol established by the Ministry of Health. After 72 h post-admission, subjects were re-examined for galectin-3 levels and LVEDV. Data were analyzed using STATA™. RESULTS: A total of 45 research subjects were analyzed. Bivariate analysis of the difference of galectin-3 and LVEDV was shown to be insignificant (r = 0.08), no correlation was found between galectin-3 level and LVEDV on ICU admission (r = 0.191), and no correlation found between galectin-3 level and LVEDV after 72 h of hospitalization (r=0.197). Multivariate analysis also showed that none of the variables, namely, difference of galectin-3 level, age, gender, troponin I, SOFA, and Charlson scores had statistically significant correlation with LVEDV (p < 0.05). CONCLUSION: No significant correlation was found between galectin-3 level and an increase in LVEDV.